A comparison of data collected through farm management associations and the Agricultural Resource Management Survey. Issue 4 (28th October 2014) - H. Kuethe, Todd; Briggeman, Brian; D. Paulson, Nicholas; L. Katchova, Ani
Abstract : Purpose: – The purpose of this paper is to compare the characteristics of farms who participate in farm management associations to the wider population of farms at the state level. Design/methodology/approach: – Farm-level records obtained from the USDA's Agricultural Resource Management Survey (ARMS) are compared to similar data obtained from farm management associations in three states: Illinois, Kansas, and Kentucky. Findings: – Data collected through farm management associations tend to represent larger farms and a greater share of crop producers as compared to livestock producers. Association data, however, capture a greater share of younger farm operators. Originality/value: – This is the first study to compare farm statistics from several farm management associations to ARMS, and the study confirms the findings of existing studies of prior USDA surveys.